Kinematics of Crystal Growth in Single‐Seal Syntaxial Veins in Limestone ‐ A Phase‐Field Study. Issue 10 (28th September 2021) - Späth, Michael; Spruženiece, Liene; Urai, Janos L.; Selzer, Michael; Arndt, Max; Nestler, Britta
Abstract: Building on recent developments in phase‐field modeling of structural diagenesis, we present an analysis of single‐seal syntaxial calcite vein microstructure in a variety of limestones. We focus on the effects of fracture aperture, intergranular versus transgranular fracturing, crystal habit and the presence of second phases in the host rock, to systematically investigate a simplified set of models covering the main classes of limestone in 2D. We incorporate the kinematic process of growth competition between differently oriented crystals, growth rate anisotropy between rough and faceted crystal surfaces and different growth rates on intergranular to transgranular fractures. Results show that within the considered parameter space we can reproduce a wide range of vein microstructures in limestone known in nature, such as stretched crystals, wide‐blocky veins, and elongated crystals. We identify five archetypes of vein microstructures in limestones, which are diagnostic for different kinematics and evolution of transport processes and illustrate the effect of key parameters in microstructure maps. We show how syntaxial veins with median line form after intergranular fracturing, while stretched crystals indicate transgranular fracturing. Intergranular fracturing leads to stronger growth competition and more prominent CPO in syntaxial veins. Our results can be extended to 3D to include multiple crack‐seal events, pore‐space cementation and simulation of fluid flow, providing a generic platform for modeling structural diagenesis in limestones. Plain Language Summary: Fractures are ubiquitous in in the earth crust, forming important pathways for geothermal fluids. This fluid is often supersaturated, allowing crystals to grow in the open fractures which leads to fracture healing over time. During this self‐sealing of the fractured rock the permeability and strength of the rock change with many important consequences for subsurface engineering. In this study, we simulate the complex growth process and show how different crystal structures (e.g., stretched, blocky) form in open fractures in different types of limestone and compare our results to natural rock samples. We test different factors on how they affect the crystal morphology as fracture type (crack cuts though grain or along grain boundaries), opening width of the fracture, and coated grain surfaces (which can reduce the crystal growth rate). We are able to reproduce a wide range of crystal structures which occur in natural limestone, and present a framework for interpreting the evolution process of calcite veins in limestones. The systematic data analysis provides valuable insight in structure‐property linkages enabling a prediction of fracture healing mechanisms. Key Points: Systematic phase‐field study captures formation of a wide range of single seal veins in limestones and provides insight to fracture healing Effects of different parameters are illustrated in morphology maps and show diagnostic microstructures Transgranular fracturing leads to stretched crystals and intergranular fracturing leads to more prominent CPO in syntaxial veins